2024
DOI: 10.1159/000535523
|View full text |Cite
|
Sign up to set email alerts
|

TLR10: An intriguing Toll-like receptor with many unanswered questions

Carolina Rego Rodrigues,
Yadu Balachandran,
Gurpreet Kaur Aulakh
et al.

Abstract: Background: Toll-like receptors (TLRs) are one of the first pattern recognition receptors (PRRs) found in the innate immune system. The TLR family has 12 members (TLR1-TLR9, TLR11-TLR13) in mice and 10 members (TLR1-TLR10) in humans, with TLR10 being the latest identified. Summary: Considerable research has been performed on TLRs, however, TLR10 is known as an orphan receptor for the lack of information on its signalling, role, and ligands. Even though there are recent studies pointing towards the potential TL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 62 publications
0
2
0
Order By: Relevance
“…TLR13 is specific for rRNA regions, particularly certain 23S rRNA motifs found in bacteria [105,106]. Human TLR10 has been shown to bind to dsRNA in vitro at acidic pH, suggesting it has an endosomal location [107] in addition to having a plasma membrane localization [108]. The exact mechanisms of TLR10 are somewhat unclear and it is suspected to have both pro-and anti-inflammatory properties (reviewed in [108]).…”
Section: Tlr Signaling In Sle-an Update On Recent Findingsmentioning
confidence: 99%
See 1 more Smart Citation
“…TLR13 is specific for rRNA regions, particularly certain 23S rRNA motifs found in bacteria [105,106]. Human TLR10 has been shown to bind to dsRNA in vitro at acidic pH, suggesting it has an endosomal location [107] in addition to having a plasma membrane localization [108]. The exact mechanisms of TLR10 are somewhat unclear and it is suspected to have both pro-and anti-inflammatory properties (reviewed in [108]).…”
Section: Tlr Signaling In Sle-an Update On Recent Findingsmentioning
confidence: 99%
“…Human TLR10 has been shown to bind to dsRNA in vitro at acidic pH, suggesting it has an endosomal location [107] in addition to having a plasma membrane localization [108]. The exact mechanisms of TLR10 are somewhat unclear and it is suspected to have both pro-and anti-inflammatory properties (reviewed in [108]). Interestingly, in relation to SLE, Lee et al (2018) showed that the binding of TLR10 to dsRNA activated the MyD88 signaling pathway and suppression of IRF7-dependent type I IFN expression as well as inhibition of TLR3 signaling through sequestering dsRNA from this receptor [107].…”
Section: Tlr Signaling In Sle-an Update On Recent Findingsmentioning
confidence: 99%